COMPARATIVE CHARACTERISTICS OF THE LAKES OF THE KARAGANDA REGION OVER THE PAST 50 YEARS (Eurasian Journal of Ecology, 2023)
The paper gives a general overview of the lakes of the Karaganda region according to the main hydrological characteristics. A comparative analysis of several morphometric indicators of medium and small lakes in the region in 1968 and 2020 was also carried out. Over the past period, the total area of ​​small lakes has not changed, but some of the lakes were dry in 1968, so the total volume of water in this group has increased by 19.7% since 1968. In medium and larger lakes, a significant change in the total area and volume of water is observed: an increase in area by 4.12% and an increase in volume by 12.6%. In the largest lakes of the region (more than 20 km2), with an increase in the area of ​​lakes by 6.5%, the volume of total water increased by 53%. Thus, despite the general increase in the average annual temperature and changes in the precipitation regime in the region, the areas of reservoirs and the volume of the total water mass have increased, while the dynamics of indicators depends on the specific area of ​​​​the reservoir.Key words: lakes, hydrology, morphometric indicators, area of ​​lakes, volume of water, Karaganda region.